Sustainable Development: Towards A New Paradigm For India - Srivastava, Raghav (European Journal of Sustainable Development, 2016)
Using the Nyamjang Chhu hydropower project in northeast India, in context of the Environment Impact Assessment process in India, this paper argues that the current model of development in India needs to be re-evaluated, and the effects of cultural marginalisation and breakdown of traditional social structures and livelihoods be properly accounted for in impact assessments to achieve development that is sustainable for all stakeholders involved.